PDE4B promotes ferroptosis in nucleus pulposus cells and is involved in intervertebral disc degeneration - Weixing Xu; Rana Dhar; Danyang Zheng; Qi Peng; Yue Li; Sheng Mei; Huifang Tang (Scientific Reports)
Abstract Intervertebral Disc degeneration (IDD) is one of the leading causes of disability, and current therapies are ineffective. Phosphodiesterase 4B (PDE4B) plays an essential role in regulating the activation of nuclear factor E2-related factor 2 (﻿Nrf2), while Nrf2 regulates ferroptosis. However, it is still unknown whether PDE4B is involved in the development of IDD. In this study, we explored the role of PDE4B on ferroptosis and Nrf2 in IDD pathogenesis by in vivo and in vitro experiments. The findings suggested that the expressions of PDE4B, ASCL4, and TRFC were significantly upregulated, and the expression of Nrf2 was significantly downregulated in nucleus pulposus (NP) tissues from human IDD patients dependent on IDD degeneration. Overexpression of PDE4B (PDE4B-OE) in NP cells upregulated the expression of ASCL4 and TRFC, and downregulated the expression of Nrf2. Meanwhile, the level of cytokine and oxidative stress were upregulated. Ferroptosis inhibitor Fer-1 or Nrf2 activator dimethyl fumarate (DMF) suppressed the effect of PDE4B-OE, while ferroptosis inducer elastin enhanced the effect of PDE4B-OE. In the IDD rat model, PDE4 inhibitor roflumilast, ferroptosis inhibitor Fer-1, or Nrf2 activator dimethyl fumarate (DMF) delayed IDD pathogenesis. While administration of ferroptosis inducer elastin enhanced IDD pathogenesis. Combination with PDE4B inhibitor and ferroptosis inhibitor Fer-1 significantly synergistic reversed IDD pathogenesis. While combination with PDE4B inhibitor or Nrf2 activator and elastin also decreased the degree of the IDD. The IHC suggested PDE4 inhibitor downregulated the expression of ASCL4 and TRFC. However, the combination effect of the Nrf2 activator was not obvious. Our study suggested that aberrant PDE4B activation in NP tissues induces pathological changes in IDD mediated by ferroptosis, and PDE4 inhibitor reveres the process of IDD by suppressing ferroptosis, and has a synergic effect with ferroptosis inhibitor. So PDE4B inhibition may be a potential therapeutic strategy for IDD.